Reconceptualizing Investor Protection Through Arbitration: Legal Challenges and the Future of Investment Dispute Resolution in Indonesia - Ikhsan Sahriyan; M. Fazli Pratama; Rahman Al Fauzi Siregar; Siti Salmiah Dalimunthe; Muhammad Ikhlas Bin Rosele (ISNU Sumatera Utara, 2026)
This study examines the strategic role of arbitration as a mechanism for resolving investment disputes in Indonesia. Investment plays a vital role in national economic development, yet it inherently carries the potential for conflicts between investors, business partners, and the government. Conventional litigation often proves lengthy, costly, and insufficiently confidential, prompting a demand for alternative dispute resolution. This research employs normative legal methods (doctrinal research), using statute and conceptual approaches to analyze relevant legislation, including Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution and Law No. 25 of 2007 on Investment, as well as arbitral awards and scholarly literature. The study systematically identifies legal issues, collects and classifies legal materials, and applies qualitative analysis through grammatical, systematic, and teleological interpretation. Findings indicate that arbitration provides legal certainty, procedural flexibility, neutrality, and enforceable outcomes, strengthened by Indonesia’s ratification of the 1958 New York Convention. Despite legal and practical challenges, arbitration effectively protects investor rights, supports a conducive investment climate, and enhances Indonesia’s economic competitiveness. Recommendations include strengthening institutions, human resources, and future research aligned with digital and cross-border investments. Unlike previous studies that primarily discuss arbitration as a procedural alternative to litigation, this article reconceptualizes arbitration as an institutional safeguard for investor protection within contemporary investment governance. The study argues that the effectiveness of arbitration depends not only on procedural efficiency but also on the coherence between domestic investment law, international arbitration standards, judicial support, and regulatory certainty. Accordingly, this article contributes to arbitration scholarship by proposing an integrated legal framework capable of strengthening investor confidence while preserving national regulatory sovereignty.